Dietary Intake and Food Sources of Total and Individual Polyunsaturated Fatty Acids in the Belgian Population Over 15 Years Old. Issue 7 (16th April 2013) - Sioen, Isabelle; Vyncke, Krishna; De Maeyer, Mieke; Gerichhausen, Monique; De Henauw, Stefaan
Abstract: Advances in our knowledge of the physiological functions of dietary polyunsaturated fatty acids (PUFAs) have led to an increased interest in food sources and the level of dietary intake of these nutrients. Up to now, no representative data was available for the Belgian adult population. This study aimed to describe data on the intake and food sources of total and individual omega‐6 and omega‐3 PUFA for the Belgian population over 15 years old. PUFA intakes were assessed for 3, 043 Belgian adults, based on two non‐consecutive 24 h recalls. Usual intakes were calculated using the multiple source method. The results showed that the intake of linoleic acid (LA) is in accordance with the recommendation for almost all Belgian adults. However, the intake of omega‐3 PUFA is suboptimal for a large part of the studied population and also the intake of total PUFA should be increased for a part of the population. The main food source of LA and α‐linolenic acid (ALA) was the group of fats and oils (60.6 % for LA and 53.1 % for ALA). Fish and fish products were the most important sources of long chain omega‐3 PUFA. Age influenced fatty acids intake, with higher intake of omega‐3 PUFA in the older age groups. To fill the gap between the intake and recommendation of total PUFA, and in particular omega‐3 PUFA, sustainable strategies and efficient consumer communication strategies will be needed.